Optimization of Legal Policies Against Trademark Rights Violations Based On Restitution - Grace Putri Hastino; Elina Fauziah; Vina Maylani; Teddy Asmara; Ari Nurhaqi (Yayasan Adra Karima Hubbi, 2025)
Background. Trademark counterfeiting is a significant violation of Intellectual Property Rights (IPR)and has emerged as an important issue within the legal and economic framework Purpose. This research aims to analyse the basic concept of trademark infringement and how to optimize legal policy against restitution-based trademark infringement. Methods. Using normative juridical research method (doctrinal) with a descriptive and analytical nature, data collection techniques are done through literature review, content analysis, and case studies with qualitative analysis. Result. The results show that trademark infringement is an economic criminal offence that significantly harms the owner. Law Number 20 of 2016 still focuses on criminal punishment without guaranteeing the recovery of victims' losses. Conclusion. Therefore, restitution as part of criminal sanctions is very important to realise complete justice. Implementation. By integrating restitution into the criminal process, Indonesian law can better protect intellectual property rights and provide fair and adequate protection for brand owners.